2005
DOI: 10.1123/ijsnem.15.6.573
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbohydrate Intake on Half-Marathon Performance of Well-Trained Runners

Abstract: Eighteen highly-trained runners ran two half marathons in mild environmental conditions, 3 wk apart, consuming either 426 +/- 227 mL of a flavored placebo drink (PLACEBO) or an equivalent volume of water (386 +/- 185 mL) and a commercial gel (GEL) supplying 1.1 +/- 0.2 g/kg body mass (BM) carbohydrate (CHO). Voluntary consumption of this fluid was associated with a mean BM change of approximately 2.4%. Runners performed better in their second race by 0.9% or 40 s (P = 0.03). Three runners complained of gastroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
40
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 25 publications
(60 reference statements)
1
40
3
Order By: Relevance
“…This result is in agreement with a previous report of a higher prevalence of GI distress in half-marathon runners after gel administration compared with the use of water only (Burke et al, 2005). Symptoms reported in the current study included flatulencies, bloating, and the urge to defecate, which are common GI complaints in endurance sports (Brouns et al, 1987).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This result is in agreement with a previous report of a higher prevalence of GI distress in half-marathon runners after gel administration compared with the use of water only (Burke et al, 2005). Symptoms reported in the current study included flatulencies, bloating, and the urge to defecate, which are common GI complaints in endurance sports (Brouns et al, 1987).…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, Burke et al (2005) reported no significant performance benefit of GEL compared with water only during a half-marathon run (Burke et al, 2005). It is noteworthy that several runners using GEL reported gastrointestinal (GI) discomfort, which was found to have a negative impact on half-marathon performance (Burke et al, 2005).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The measurement of the former, together with the continuous profiling of T c , provides insights to pacing in relation to T c during a competitive half marathon race in the heat. The latter permits precise data describing fluid intake during a half marathon race to ascertain its influence on T c during outdoor distance running, as prior studies with accurate fluid intake quantification were not conducted in actual races (Burke et al 2005;Passe et al 2007). Although logistical challenges, lack of control and other limitations exist in field research, its key ecological advantage is that volunteers are motivated to perform to their maximum capacity during actual racing, in contrast to laboratory investigations.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, evidence of enhanced performance when carbohydrate is consumed during a variety of such exercise protocols is perplexing (for a review, see Burke, Wood, Pyne, Telford, & Saunders, 2005). Findings of a lack of improvement of a 1-h cycling protocol with glucose infusion (Carter, Jeukendrup, Mann, & Jones, 2004b) but benefits from carbohydrate ingestion (Carter, Jeukendrup, & Jones, 2004a) created an intriguing hypothesis that the central nervous system might sense the presence of carbohydrate via receptors in the mouth and oral space, promoting an enhanced sense of well-being and improved pacing.…”
mentioning
confidence: 99%